Analisis Kesesuaian Realisasi di Lapangan terhadap Rencana Penambangan Bulan Maret 2025 di Pit P3BK4 PT Tama Raya provinsi Kalimantan timur - Pasaribu, Aldo Radot Hamonangan; Hutajulu, Yossa Yonathan; Wiryanto, Yustinus Hendra; Noveriady, Noveriady; Usup, Hepryandi Luwyk Djanas (Pusat riset dan Inovasi Nasional, 2026)
This study was conducted to evaluate the level of conformity between actual mining activities in March 2025 and the monthly sequence design plan at PT Tama Raya's P3000BK14 pit. The evaluation focused on geometric deviations, volume achievement, and changes in field conditions that influenced these discrepancies. The data used included the sequence design, actual topography from the TLS (Low-Scale Land Survey), and weekly production realizations. The results showed significant discrepancies between the planned and actual operations in weeks 2 and 4, primarily in the form of overcuts, undercuts, non-designed contour changes, thinning of the coal seam, and hydrological obstacles such as ponding and unstable drainage. The R2 sequence redesign in week 4 proved to improve the overburden excavation flow but did not fully restore coal access due to persistent geological and water conditions. These findings emphasize the need for more rapid topographic updates, more intensive water handling, and interdepartmental coordination to ensure better synchronization of plans and operations.